Assessing the Efficiency of the District Election Committee in the 2024 General Elections: Evidence from Ciwandan, Cilegon City - Ahmad Zainuri (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the performance of the District Election Committee in Ciwandan District, Cilegon City. A qualitative descriptive approach was employed, with performance measured based on (S. Robbins et al., 2013) criteria, which include quality, quantity, timeliness, effectiveness, and efficiency. Data were collected through observation, interviews, and documentation, and analyzed using the stages of Data Condensation, Data Display, and Conclusion Drawing.The results indicate that the performance of the District Election Committee during the 2024 simultaneous general elections in Ciwandan District was generally in accordance with the planned schedule. However, several issues were identified, such as logistical shortcomings, including the insufficient supply of ballot papers and instances of ballot exchanges with other polling stations during the election process. Furthermore, 97 individuals were found to be unregistered in the voter list, indicating inadequacies in voter list updates a key responsibility of the District Election Committee. The study also highlights the insufficient commitment of committee members, as some members had other jobs outside the committee, leading to suboptimal performance due to task delegation to less knowledgeable members.